Tingkat Penerapan Pemupukan Dengan Empat Tepat (4T) oleh Petani pada Tanaman Padi Sawah di Desa Kebonagung Kecamatan Imogiri Kabupaten Bantul - Fatimah, Nur (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2020)
Increasing rice productivity can be done by applying new superior seeds, application of Four Appropriate (4T) fertilizers, and good management of rice cultivation and soil health by maximizing organic matter or biological agents. The purpose of this study was to determine the level of farmer application of four-right fertilization (4T) in lowland rice plants in Kebonagung Village, Imogiri District, Bantul Regency. This study was conducted in February-June 2019 in Kebonagung Village, District, Imogiri, Bantul Regency. The method used is observation and interviews with a questionnaire instrument on the respondents who are determined by simple random sampling. According to Sugiyono (2001: 57) it is stated simple (simple) because the sampling of members of the population is done randomly without paying attention to the existing strata in the population. In this study, data collection on farmers in Kebonagung Village was then carried out random sampling. Furthermore, the data were analyzed using descriptive analysis, where the data were in the form of quantitative and qualitative data. Descriptive analysis is intended to describe the characteristics of each research variable, by presenting the data in a frequency distribution table, calculating the average value, total score, and level of achievement of the respondents and interpreting them. Descriptive analysis was carried out to determine the level of each sub-variable under study by giving scores on each indicator. The results of the study showed that the level of application of four-precise fertilization (4T) in lowland rice in the village of Kebonagung was classified as low, with an achievement level of 25.58%. The level of farmer application of appropriate type (source) fertilization was 34.52%, 46.75% on time, 5.56% on time, and 15.48% in the right way (place)